On some interesting properties for a new subclass of multivalent functions - Ahmad, M.Z.; Ibrahim, R.W.; Al-Janaby, H.F. (World Scientific Publishing, 2016)
In this paper, we establish a new subfamily ℘p(τ, α, β) of multivalent functions with negative coefficients that involve certain linear operator. We first investigate sharp results concerning coefficients, then obtain the distortion theorem, radius of convexity and close-to-convexity, closure theorem, neighborhood property, partial sums and integral representation.